Analyse af adfærd i idrætsfaciliteter - Gade, Rikke; Christensen, Cecilie Breinholm; Krogh, Rasmus; Moeslund, Thomas B.; Harder, Henrik (Forum for Idræt, 2013)
Analysis of Behaviour in Sports Facilities This article builds upon existing research at Department of Architecture, Design and Media Technology, Aalborg University. It deals with research based methods and technologies for analysing behaviour in sports facilities. There is a need to study how existing and new sports facilities can be optimised in accordance with the more individualised and varied practice of sports today. Tracking technologies, such as RFID-technology and thermal video analysis, give the possibility to gain knowledge on the use of indoor sports facilities by tracking movements and positions of people in time and space. In combination with more qualitative methods and existing theory it is possible to gain an understanding of the relation between social and spatial aspects of sports facilities, and thereby to analyse actual behaviour in sports facilities. On a practical level, such analyses can be used as input for improvements in terms of administration and design of sports facilities, as well as in sports training and coaching. On a research level, such analyses can be applied in further development of the methods and technologies presented here, as well as in further research of both the spatial and social aspects of sports and sports facilities.